Tax instrument of fiscal policy under conditions of digitalization of fiscal space (World of finance, 2019)
Introduction. Nowadays information technologies and digital assets came into our lives, generating risks and potential threats to society. A structure of rational fiscal policy in such risks and threats is a key issue for the current policy of the country.Purpose. The purpose of the article is to study methodological approaches to understand the essence and nature of the taxation of individual incomes under the conditions of an innovative digital trend in society, which can be used to implement a fair fiscal policy in Ukraine.Methods. The author used scientific methods such as historical, abstraction, deduction, comparison, analysis, systematization and others.Results. It was established that digitalization processes, on the one hand, can stimulate avoidance and tax evasion, and, on the other hand, can increase the effectiveness of fiscal policy. Digital technologies weaken informational limitations in the implementation of tax control to identify the present economic results of taxpayers, and also allow to implement a complex tax system at lower costs.Conclusions. The fairness of taxation in digitalized fiscal policy and space should be based on ensuring a relatively equal environment for individuals as a result of the comprehensive taxation of various types of individual income - labor, capital and inheritance. Despite this, the use of an information resource in fiscal policy will help to achieve a balance between efficiency and fairness of taxation.